Assessment frameworks and teaching modules that promote student learning in immersive short-term international study experiences : final report. - Cushing, Debra; Pennings, Mark; Dyson, Clare; Gomez, Rafael; Willox, Annabelle (Dept of Education and Training Australia, 2017)
Final report from a project that developed new forms of assessment that could improve the quality of university student learning in international short-term study tours. Researchers wanted to maximise the benefits for students in this immersive study context to enhance their learning and provide them with skills that could improve their opportunities of securing a career in the competitive workplace. The project encouraged reflective pedagogy to ensure student education during outbound international short-term study experiences, especially in relation to intangible learning outcomes. Data collected informed the development of intangible learning modules as a form of assessment to enhance learning experiences and assist students to develop discipline-related knowledge and personal qualities that will prepare them for employment.